2022
DOI: 10.1007/s00421-022-04956-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function and its association with systemic artery function and stiffness in older adults with and without mild cognitive impairment

Abstract: Purpose Our aim was to compare cerebrovascular and systemic vascular function between older adults with and without mild cognitive impairment (MCI), and to determine which measures of vascular function best predict the presence of MCI. Methods In 41 adults with MCI and 33 adults without MCI (control) we compared middle cerebral artery velocity (MCAv) and cerebrovascular pulsatility index (PI) at rest, cerebrovascular reactivity to CO2, and responsiveness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…When AD and hypotensive events (total episodes of BP instability) were combined together significant positive correlations were observed with cfPWV, which is a prognostic risk factor for cardiovascular disease (Vlachopoulos et al, 2010). A recent study raised the possibility that vascular stiffness contributes to altered cerebrovascular hemodynamics and impaired cognitive function in older adults (Bailey et al, 2022). Although our findings suggest a stronger link between low BP and CVR outcomes, the daily fluctuations in BP experienced by this population likely both contribute to the deterioration in cerebrovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When AD and hypotensive events (total episodes of BP instability) were combined together significant positive correlations were observed with cfPWV, which is a prognostic risk factor for cardiovascular disease (Vlachopoulos et al, 2010). A recent study raised the possibility that vascular stiffness contributes to altered cerebrovascular hemodynamics and impaired cognitive function in older adults (Bailey et al, 2022). Although our findings suggest a stronger link between low BP and CVR outcomes, the daily fluctuations in BP experienced by this population likely both contribute to the deterioration in cerebrovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…When AD and hypotensive events (total episodes of BP instability) were combined together significant positive correlations were observed with cfPWV, which is a prognostic risk factor for cardiovascular disease (Vlachopoulos et al, 2010). A recent study raised the possibility that vascular stiffness contributes to altered cerebrovascular hemodynamics and impaired cognitive function in older adults (Bailey et al, 2022).…”
Section: Taumentioning
confidence: 99%
“…We observed increases in functional measures of peripheral endothelial function as well as in biochemical markers of endothelial function in the present study. Arterial stiffness has been implicated in the development of dementia (44), as it is associated with age-related differences in cerebrovascular conductance (27). In addition, patients with diabetes also demonstrate increased PI in the common carotid artery (45).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Csipo et al (2019) have supported this by indicating that vascular-related risk factors predicted cognitive dysfunction in older adults [ n = 29 (28, White)]. This relationship is suspected to be multifaceted, but an overall consequence of aging includes the disruption to the blood brain barrier ( Chernick et al, 2019 ; Nation et al, 2019 ; Montagne et al, 2020 ; Pluvinage and Wyss-Coray, 2020 ; Nelson, 2022 ; Oudbier et al, 2022 ), which may be exacerbated by increased peripheral arterial stiffness and endothelial dysfunction ( Winder et al, 2021 ; Bailey et al, 2022 ). Furthermore, a product of peripheral vascular dysfunction includes the attenuation of BDNF production considering that, as previously mentioned, BDNF is produced by the hippocampus as well as non-neuronal tissues such as vascular endothelial cells ( Nakahashi et al, 2000 ; Lemos et al, 2016 ).…”
Section: Introductionmentioning
confidence: 88%
“…Peripheral organ health is a key factor in terms of influencing overall brain health and function ( Pluvinage and Wyss-Coray, 2020 ; Winder et al, 2021 ; Huuha et al, 2022 ; Nelson, 2022 ; Oudbier et al, 2022 ; Saiyasit et al, 2022 ). In particular, numerous studies have demonstrated the importance of peripheral vascular health as it relates to the maintenance of cognitive function and prevention of neurodegeneration ( Csipo et al, 2019 ; Albrecht et al, 2020 ; Winder et al, 2021 ; Bailey et al, 2022 ; Nelson, 2022 ; Saiyasit et al, 2022 ), especially given the continued increase in prevalence of modifiable risk factors like obesity that (in)directly affect vascular function ( Kim and Kim, 2021 ; Koenen et al, 2021 ). Vascular dysfunction is currently the earliest detectible and fastest changing biomarker related to the onset of neurodegeneration ( Iturria-Medina et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%